Effect of pretransplant preconditioning by whole body hyperthermia on islet graft survival. - Brandhorst, H; Olbrich, M; Neumann, A; Jahr, H; Brandhorst, D (2007)
Previous observations in heat-shocked pig islets revealed the ambivalent character of the stress response simultaneously inducing processes of protection and apoptosis. To clarify whether the proapoptotic character of the stress response is reduced in heat-exposed islets still embedded in their native environment, hyperthermia was performed in the present study either as whole body hyperthermia (WBH) prior to pancreas resection or as in vitro heat shock (HS) after isolation. HS (42 degrees C/45 min) was induced in donors 12 h before isolation (WBH, n = 32) or in freshly isolated islets prior to 12 h of culture at 37 degrees C (in vitro HS, n = 25). Islets continuously incubated at 37 degrees C served as controls (n = 34). Proinflammatory treatment was performed with H2O2, DETA-NO, or a combination of IL-1beta, TNF-alpha, and IFN-gamma. Quality assessment included islet yield, viability staining, static glucose incubation, and nude mouse transplantation. WBH was significantly less effective than in vitro HS to induce HSP70 overexpression and to increase islet resistance against inflammatory mediators. Although characterized by an unaltered Bax to Bcl-2 ratio, islets subjected to WBH partially failed to restore sustained normoglycemia in diabetic nude mice. The inflammatory response observed in the pancreas of WBH-treated rats was associated with significantly reduced viability that seems to have a higher predictive value for posttransplant outcome compared to islet in vitro function or mitochondrial activity. In contrast, in vitro HS significantly decreased transcript levels of Bcl-2, but did not affect posttransplant function compared to sham-treated islets. These findings suggest that WBH is primarily associated with increased necrosis as a secondary tissue type-specific effect of pancreas damage while in vitro HS mainly induces apoptosis.